Travel vision : a practical guide for the travel, tourism, and hospitality industry - Semer-Purzycki, Jeanne (Upper Saddle River, NJ : Prentice Hall, 2000)
Tourism geography. Domestic air travel. International air travel. Computer technology. Accommodations. Tours and vacation packages. Cruise travel. Car and rail travel...
Keywords: Tourism; Tourism -- Vocational guidance